Rheumatic paraneoplastic syndromes - A clinical link between malignancy and autoimmunity - Manger, Bernhard; Schett, Georg (Clinical Immunology, 2017)
Paraneoplastic syndromes are rare but can have enormous clinical impact on diagnosis and outcome of neoplastic diseases. The rheumatologist should be familiar with a few typical musculoskeletal manifestations of malignancies to be able to diagnose them early for a timely initiation of anti-tumour therapies. This review describes the characteristic features of various paraneoplastic arthritides and vasculitides, cancer-associated myositis, hypertrophic osteoarthropathy, and tumour-induced osteomalacia. In addition, the current knowledge about underlying pathomechanisms of these syndromes is discussed.
EVALuna2:13435